PENYULUHAN STRATEGI PEMASARAN PRODUK UMKM DI DESA SUNGAI BAUNG KECAMATAN MUARA BULIAN KABUPATEN BATANG HARI PROVINSI JAMBI - Laksono, Bangun Joko; Dewi, Ratna; Enita, Enita; Uliya, Uliya; Darma, Budi (Nindikayla Institute, 2024)
Factually the value of entrepreneurship can be utilized as part of a marketing strategy. The objectives of this activity include: 1). Describe the business conditions of MSMEs in Sungai Baung Village? ; 2). Describe the form of MSME Marketing strategy in Sungai Baung Village?. Empirical studies show the urgency of marketing strategy practices to get a positive trend of small and medium business development. With the holding of this community service, it was concluded that service activities on counseling marketing strategies to MSMEs in Sungai Baung Village could add insight and knowledge to MSME actors in developing their businesses